The Influence of Service Quality and Trust on Mediated Loyalty Customer Satisfaction - Rizkha Hayunda Putri Ferenika; Survival; Dharmayanti Pri Handini (Journal of Management Research and Studies, 2024)
This study aims to determine the influence of service quality and trust on customer loyalty, mediated by customer satisfaction. The study was conducted on customers of Pedis Care in Malang City. The population in this study consists of all customers who have used Pedis Care's services during the year 2023. The sampling technique used was total sampling, with a total of 76 respondents. Data collection was carried out through the distribution of questionnaires, and the data obtained were processed using Smart Partial Least Square (PLS) software. The results of the study indicate that service quality and trust have a positive and significant effect on customer satisfaction. Additionally, customer satisfaction positively and significantly influences customer loyalty. Furthermore, customer satisfaction is proven to mediate the effect of service quality and trust on customer loyalty. Therefore, it can be concluded that improving service quality and customer trust at Pedis Care can indirectly increase customer loyalty through enhanced customer satisfaction.